1968
DOI: 10.1002/rds196837698
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Auroral Radio Absorption Between Conjugate Points

Abstract: Observations with riometers at four pairs of conjugate, or nearly conjugate, stations have been studied to determine how closely auroral radio absorption is correlated at magnetically conjugate points. The available evidence suggests that, if the loss of correlation due to imperfect siting of the stations and to the movement of conjugate points is taken into account, the conjugate correlation remains suprisingly good to high latitudes and perhaps throughout the auroral region. It is suggested that conjugate po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…At slightly lower latitudes Little et al [1965] found the position of maximum correlation to vary from event to event. Hargreaves and Ecklund [1968] reported significant variations in correlation distances for absorption events. Hargreaves [1969b] found indications that the position of the Byrd conjugate was more often north and somewhat west of Great Whale River, although on very many occasions it appeared in the opposite direction.…”
Section: Absorption Analysismentioning
confidence: 98%
“…At slightly lower latitudes Little et al [1965] found the position of maximum correlation to vary from event to event. Hargreaves and Ecklund [1968] reported significant variations in correlation distances for absorption events. Hargreaves [1969b] found indications that the position of the Byrd conjugate was more often north and somewhat west of Great Whale River, although on very many occasions it appeared in the opposite direction.…”
Section: Absorption Analysismentioning
confidence: 98%